Pentecostals and Interreligious Conflict in India: Proselytization, Marginalization, and Anti-Christian Violence - Bauman, Chad M. (PentecoStudies, 2017)
Anti-Christian violence in India has increased dramatically since the late 1990s, and there are now, on average, several hundred attacks on Christians every year. In this violence, Pentecostals are disproportionately targeted. This article begins by providing the historical and political context for anti-Christian violence, and then seeks to account for the disproportionate targeting of Pentecostals. While there are certain obvious factors, such as the more assertive evangelizing of Pentecostals (and other Evangelicals) vis-à-vis mainstream Christian groups, the article explores and highlights several less obvious factors, and in particular the peculiar social, theological, ecclesiastical and liturgical aspects of Pentecostalism that make this form of Christianity particularly objectionable to Hindu nationalists, as well - importantly - as to many mainstream and upper-caste/upper-class Indian Christians.